Avaliação do efeito do agonista do receptor de estrogênio acoplado a proteína g (g1) sobre o tônus e reatividade vascular coronariana em ratos normotensos de ambos os sexos - Debortoli, Angelina Rafaela (2015)
Cardiovascular diseases represent the main cause of death in developed countries. Moreover, the incidence of cardiovascular diseases increases significantly in postmenopausal women, possibly because of a reduction of estrogen levels. Estrogens exert their genomic effects by activating their nuclear receptors α e β, besides no genomic effects via activation of a third estrogen receptor, recently released, named estrogen receptor coupled to protein G (GPER), also known as GPR30. The GPER function were described mainly in the cardiovascular system. Some studies in isolated coronary vessels, demonstrate that the GPER activation, promotes dependently or independently, the vasodilatationin the endothelium. However, in the coronary bed, this receptor role was not described. The aim of our work was to analyze the action of G1, the specific agonist of GPER in both sexes of normotensive rats‟ coronary vascular bed. 10-month-old Wistar Rats, were divided into two groups: males and females. The animals were anesthetized, their chests were opened, their hearts were removed, and rapidly perfused with nourishing solution at 37º C with constant flow of 10 mL/min, according to Langendorff‟s technique. After a period of 40 min of stabilization, the pressure of coronary perfusion was determined. Dose response curve G1 (600 a 10.000 nM) was performed before and after the follow protocols: inhibition of the nitric oxide synthase enzyme (NOS) with L NAME, inhibition of cyclooxygenase enzyme (COX), inhibition of cytochrome enzyme P450 (CYP), associated inhibition of NOS and COX, associates inhibition of NOS and CYP, triple inhibition of NOS, COX and CYP, blockade of potassium channels with tetraethylammonium (TEA) and blockade with GPER specific antagonist (G36). Besides these protocols, the animals‟ systolic blood pressure was measured through tail plethysmography. We also dissected their anterior and septal descending coronaries to perform Western Blotting in order to evaluate the GPER expression, antioxidant enzymes (SOD e catalase) and subunit of NADPH oxidase. Oxidative stress in coronary arteries was evaluated through fluorescence to the DHE. Our results show the existence of a difference in PAS and PPC between males and females. PAS was higher in males while PPC was higher in females. G1 promoted vasodilatation in rats‟ coronary bed in both sexes, being this response more pronounced in females. GPER, SOD and catalase expression was similar in both groups. Whereas gp91phox expression and oxidative stress were larger in males. The dilatation to G1 in females was reduced after individual inhibition of NOS, COX and CYP, after combined inhibition of NOS + CYP and after triple inhibition of NOS + COX + CYP. Using G36 in experimental preparation, the vasodilatation in this group was reverted into vasoconstriction. After using TEA, dilatation in males and females was larger. Relaxation was reduced in males after individual inhibition of COX and CYP and after combined inhibition of NOS + COX. The use of G36 abolished relaxation in this group. Based on the results, we concluded that G1 expanded the Wistar rats coronary vascular bed in both sexes and this response is less pronounced in males, probably because in this group the production of reactive species of oxygen is larger. Furthermore, NO does not participate in the response of relaxation induced by G1 in males. The three endothelial autacoids (NO, PGI2 e EDHF) seem to mediate the relaxation induced by GPER agonist in females. These findings can contribute to a better understanding of G1 action on cardiovascular system, in order to make it a potential drug therapy to be used in postmenopausal period, based on the presented effects on coronary bed.